A survey of node localisation algorithms in wireless sensor networks. (3rd February 2022) - Kaur, Amanpreet; Gupta, Govind P.; Mittal, Sangeeta
Wireless sensor networks (WSN) detect and monitor various physical attributes from the environment, convert the observation into information and send it wirelessly to base station/sink. In most of applications of WSNs, localisation, that is, finding location of nodes sending information, is also required to be done for better inferencing. In this paper, we present a review of existing literature related to WSN node localisation problem. Firstly, an introduction on wireless sensor networks and its challenges are mentioned. Then, issues of localisation algorithms are discussed. The paper also discusses different localisation algorithms and their categorisation based on precision/hardware requirement, localisation algorithms can be categorised into two groups such as range-based and range-free algorithms. Various range-based and range-free algorithms with their merits and demerits are summarised and a list of research gaps is discussed.